Effect of water absorption on the mechanical properties of nanoclay filled recycled cellulose fibre reinforced epoxy hybrid nanocomposites - Alamri, Hatem; Low, It Meng (Elsevier Ltd, 2013)
Recycled cellulose fibre (RCF) reinforced epoxy/clay nanocomposites were successfully synthesized with different weight percentages (0%, 1%, 3% and 5%) of organoclay platelets (30B). The objective of this study was to investigate the effect of water absorption on the physical and mechanical properties of the RCF reinforced epoxy/clay nanocomposites. TEM images indicated a well-intercalated structure of nanoclay/ epoxy matrix with some exfoliated regions. Water absorption was found to decrease as the clay content increased. The flexural strength, flexural modulus and fracture toughness significantly decreased as a result of water absorption. However, the properties of impact strength and impact toughness were found to increase after exposing to water. The addition of nanoclay slightly minimized the effect of moisture on the mechanical properties. SEM images showed that water absorption severely damaged the cellulose fibres and the bonding at fibres–matrix interfaces in wet composites.